2017
DOI: 10.1021/acscatal.7b01499
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Production of Lactic Acid from Acetol over Dealuminated Sn-Beta Supported Gold Catalyst

Abstract: Staged biomass pyrolysis or condensation of the pyrolysis vapor generates less complex and concentrated liquid product streams, which provide a very promising route to produce value-added chemicals. Acetol is one of the major light oxygenates in fractionated bio-oil. Here we report an efficient one-pot conversion of acetol to lactic acid, a key platform chemical and an important monomer of biodegradable polymer, in aqueous phase over a bifunctional dealuminated Sn-Beta supported gold catalyst. Under relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…occurred on both carbonyl groups, it can also undergo Cannizzaro reaction [8,9] under relatively strong alkaline support or 1,2-hydride shift upon Lewis acid [7], leading to the formation of MLA, as also evidenced from entry 7 of Table 4 in our work. All these demonstrate that the base strength in the catalyst support is the very delicate and elegant part to successfully manipulate the selectivity over the varied products.…”
Section: Reaction Pathwayssupporting
confidence: 76%
See 1 more Smart Citation
“…occurred on both carbonyl groups, it can also undergo Cannizzaro reaction [8,9] under relatively strong alkaline support or 1,2-hydride shift upon Lewis acid [7], leading to the formation of MLA, as also evidenced from entry 7 of Table 4 in our work. All these demonstrate that the base strength in the catalyst support is the very delicate and elegant part to successfully manipulate the selectivity over the varied products.…”
Section: Reaction Pathwayssupporting
confidence: 76%
“…It is highly desired to convert acetol to stable and value-added chemicals. Our recent work showed that with dealuminated Sn-beta supported gold catalyst under base-free conditions, acetol can be selectively con-verted to lactic acid [7] with a higher yield and improved catalyst stability compared to the earlier literature reports with inorganic base addition or base supported catalysts [8,9]. Herein we report that another important chemical, namely methyl pyruvate, can be synthesized from acetol via oxidative esterification over Au-based catalysts, further diversifying the applications of acetol derived from renewable biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al reported an efficient one-pot conversion of acetol to LA over a bifunctional dealuminated Sn-Beta-supported gold catalyst. 25 The synthesis process of Au/deAl-Sn-Beta catalyst mainly involves two steps, namely the SSIE procedure to form deAl-Sn-Beta zeolite and thereafter the sol immobilization method to load Au on the support synthesized before. Xia et al also reported a bimetal-modified Beta zeolite Pb–Sn-Beta catalyst synthesized by SSIE for converting carbohydrates into LA.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Most researchers have focused on enhancing the hydrogenation activity and selectively cleaving CÀCb onds to catalyze the hydrolysis of cellulose. [22][23][24][25][26] HA is currently produced mainly by oxidation of 1,2propanediol, which,i nt urn, is produced mainly from petropropylene via epoxy compounds. [18][19][20][21] For some compounds, their unsaturated C=Obond makes them exhibit special features.…”
mentioning
confidence: 99%
“…In particular, HA is an important intermediate used to produce polyols, acrolein, methylglyoxal, acetone, and lactic acid or directly used as food addictive, reducinga gent, and so on. [22][23][24][25][26] HA is currently produced mainly by oxidation of 1,2propanediol, which,i nt urn, is produced mainly from petropropylene via epoxy compounds. [25,27,28] It also can be obtained by direct conversion cellulose over Ni-based catalysts such as Ni-SnO x /Al 2 O 3 or single-atom Ni catalysts.…”
mentioning
confidence: 99%